MILITARY HISTORY OF VILLUPURAM DISTRICT ON ARCHAIC PERIOD: A STUDY THROUGH HERO STONES (International Journal of Food and Nutritional Sciences, 2022)
Hero stones are important evidence of the bravery of the people during the archaic period. Indeed, there are many hero stones available in the region of Villupuram, proving the battles, warfare, and skirmishes in this region. Furthermore, it has provided enormous warfare about ancient kings who were directly or indirectly involved in the brave act. Villupuram is a significant megalithic site where prehistoric antiquities tell the history of the past. Villupuram is the prehistoric museum where all kinds of sources are held and reflected in the monuments. While human habitation was established, the protection process was also initiated. Protecting the family, society, kings, or region was the primary act of humans back then. Over the years, those who died in battle have been honored with hero stones and the most memorable monuments.